THE DEVELOPMENT OF THE SOLAR PANEL MARKET: PROSPECTS FOR INNOVATIVE MATERIALS - Merezhko, Iuliia (European Journal of Interdisciplinary Issues, 2025)
The relevance of this study is driven by the rapid advancement of solar panel manufacturing technologies, which enhance efficiency and reduce costs. These improvements make solar energy more accessible and competitive compared to traditional energy sources. Particular attention is given to innovative materials and technologies that create new opportunities for improving solar panel performance and integrating them into architectural solutions. The study aims to identify key technological innovations in solar panel production and assess their impact on efficiency and the development of the solar energy sector. The research employs general scientific methods of cognition, including analysis, synthesis, systematization, and comparison. A review of scientific and technical sources has helped outline the main directions in solar panel technology development, while comparative analysis has provided insights into their advantages and potential implementation. Findings indicate that the use of advanced materials, such as perovskite solar cells, ensures high efficiency and flexibility at a low production cost. Bifacial solar panels, capable of absorbing light from both sides, enhance overall energy output. Organic photovoltaic (OPV) materials offer environmental safety and enable the creation of flexible designs. Additionally, the study explores the potential integration of photovoltaic materials into buildings (BIPV), which allows for the efficient use of building surfaces for energy generation. The research confirms that quantum dot solar cells optimize light absorption, while CIGS technology presents a promising direction for thin-film panel production. Transparent solar panels, which can be integrated into windows and facades, introduce new possibilities for urban design. The effectiveness of tandem solar cells, which utilize multiple layers to capture a broader light spectrum and boost overall panel efficiency, has also been validated. Thus, technological innovations in solar energy contribute to increased efficiency, reduced production costs, and greater environmental sustainability in the industry.